2020
DOI: 10.1590/1809-6891v21e-62956
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood of obtaining tender meat from confined calf

Abstract: The objective was to evaluate the main factors that influence the shear strength of meat from confined steers and the probability of obtaining soft meat. For this purpose, we evaluated the literature on carcass and/or meat of beef steers in Brazil published between January 1999 and April 2019 and extracted the content from three sections for analysis: materials and methods, results, and discussion. Pearson’s correlation was used to analyze the data, and the stepwise statistic was used to determine the proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Several efforts have been made to improve the beef quality‐related traits in beef cattle breeding programs, that is, ultrasound imaging has been widely used to measure carcass traits such as rib‐eye area, fat thickness at the rump and over the 12th‐13th ribs, and marbling (Caetano et al, 2013; Marestone et al, 2022; Yokoo et al, 2010). However, meat tenderness has not been used as a selection criterion, due to the difficulty in obtaining phenotypic information and the polygenic nature of the trait (Pacheco et al, 2020; Tizioto et al, 2013; Wheeler et al, 2010). Thus, the genetic gain for this trait would be increased by the inclusion of genomic information (Magnabosco et al, 2016; Tizioto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been made to improve the beef quality‐related traits in beef cattle breeding programs, that is, ultrasound imaging has been widely used to measure carcass traits such as rib‐eye area, fat thickness at the rump and over the 12th‐13th ribs, and marbling (Caetano et al, 2013; Marestone et al, 2022; Yokoo et al, 2010). However, meat tenderness has not been used as a selection criterion, due to the difficulty in obtaining phenotypic information and the polygenic nature of the trait (Pacheco et al, 2020; Tizioto et al, 2013; Wheeler et al, 2010). Thus, the genetic gain for this trait would be increased by the inclusion of genomic information (Magnabosco et al, 2016; Tizioto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Oliveira et al (2020) evaluated the meat of feedlot-finished Nellore cattle and found L*, a*, and b* values of 34.38, 17.92, and 9.9, respectively. In addition to the colour, the tenderness of meat is also markedly influenced by age, particularly in terms of collagen solubility (Pacheco et al, 2020). Thus, the lack of effects of PKC inclusion on tenderness (shear force) is due to the similar age of the animals at slaughter.…”
mentioning
confidence: 99%